Charged particles accumulation in drift space of warm electron beam during non-stationary virtual cathod existence - Bizyukov, A.A.; Volkov, E.D.; Tarasov, I.K. (Вопросы атомной науки и техники, 2002)
In this paper, the properties and the formation of collective electromagnetic trap for electron beam that propagates in a conducting cylinder are described. It is shown that the electron beam provides the development of an electrostatic instability in the above-mentioned conditions. The instability leads to the appearance of a non-stationary virtual cathode and the formation of electrostatic potential trap. This phenomenon takes place in the central region of the drive space where the amplitude of the electrostatic potential has two maxima. The trap confines electrons during its formation and keeps them inside the drift tube. Once seized in the trap, electrons have rather low temperature and are unstable to diocotron oscillations. During the evolution of diocotron instability the spatial charge redistribution takes place in the cross-section of the beam, which is probably connected with the drift of electrons in longitudinal magnetic field. This process is accompanied not only by azimuthal redistribution of the beam density, but also by radial transfer of electrons across magnetic field, which leads to the increase of the radial beam dimensions and to the injection of electrons onto the walls of the drift chamber. The variations of the radial beam dimensions, and, hence, the spatial charge redistribution in longitudinal direction lead to the corresponding variation of the longitudinal distribution of electric potential, and appearance of self-consistent field of 'potential pit' type in central region of the drive space.